The Λ b → Λ ∗ 1520 → N K ¯ ℓ + ℓ − $$ Λ_b→ Λ^{* }(1520)\left(→ N\overline{K}\right){\mathrm{\ell}}^{+}{\mathrm{\ell}}^{-} $$ decay at low-recoil in HQET - Diganta Das (Journal of High Energy Physics, 2020)
Abstract In this paper we discuss the Standard Model and new physics sensitivity of the Λ b → Λ ∗ 1520 → N K ¯ ℓ + ℓ − $$ Λ_b→ Λ^{* }(1520)\left(→ N\overline{K}\right){\mathrm{\ell}}^{+}{\mathrm{\ell}}^{-} $$ decay at low-recoil, where ℓ ± are massive leptons and N K ¯ = pK − n K ¯ 0 $$ N\overline{K}=\left\{{pK}^{-},n{\overline{K}}^0\right\} $$ . We provide a full angular distribution with a set of operators that includes the Standard Model operators and their chirality flipped counterparts, and new scalar and pseudo-scalar operators. The resulting angular distribution allows us to construct observables that we study in the Standard Model and in model-independent new physics scenarios. To reduce the hadronic effects emanating from the Λ b → Λ* (1520) transition form factors, we exploit the Heavy Quark Effective theory framework valid at low Λ ∗ (1520) recoil, i.e., large dilepton invariant mass squared q 2 ∼ O m b 2 $$ {q}^2\sim \mathcal{O}\left({m}_b^2\right) $$ . Working to the leading order in 1/m b and including O α s $$ \mathcal{O}\left(α_s\right) $$ corrections, we compute the ‘improved Isgur-Wise relations’ between the form factors. The relations correlate the form factors and thereby allow the description of this decay at the low-recoil region with a smaller number of independent form factors.